The psychology of social movements: a view through community work - Eulálio de Souza, Silvia Regina (Revista de Psicología, 2001)
The present research aims at investigating the reasons that impel and keep actors in community work. The target population is composed of Psychology students and popular leaders. Though marked by differences, these two groups are similar in their socio-political and affective involvement during the development of their activities.The reasons for the permanence in work in relation to the construction of knowledge, the conciousness of citizenship and for the relations based upon solidarity were analysed.It was veirified that autonomy is the main reason, for the freedon of expression and the creation of self-managing processes. Methodologies of the Communital Social Psychology practice and of Socila Movements present similarities and are complementary.A space for psychologist’s to action was confirmed as it enriches his (her) human dimension, socializes his knowledge and fosters the full bloom of potencialities in those not socialy inclusion.